The effect of perceived support on subjective well-being of academic institution staff - Najah Afina Mohd Harun; Muhammad Idris Bullare @ Bahari (Penerbit UMS, 2023)
This study aimed to examine the effects of perceived support on subjective well-being (SWB) among university staff in the context of COVID-19. The research sample comprised of 522 employees from Malaysia public universities, which included both academicians and non-academicians. The respondents completed two online questionnaires. Statistical analyses used were descriptive statistics and regression. The results revealed that perceived support directly affects higher institution employees’ subjective well-being. The study confirmed the importance of perceived support for university employees’ subjective well-being.